In vitro propagation of infectious myonecrosis virus in C6/36 mosquito cell line. Issue 7 (25th February 2021) - Santhosh Kumar, S.; Sivakumar, S.; Abdul Majeed, S.; Vimal, S.; Taju, G.; Sahul Hameed, A. S.
Abstract: Infectious myonecrosis (IMN) is an important shrimp viral disease caused by infectious myonecrosis virus (IMNV). Based on previous reports, an attempt was made to propagate IMNV in apparently healthy C6/36 subclone of Aedes albopictus cell line. The confirmatory assays such as RT‐PCR, real‐time PCR and bioassay revealed that C6/36 cells were found to be susceptible to IMNV and these cells could be used easily for isolation and propagation of IMNV. The results of real‐time PCR assay showed that a lower CT value of 22.25 in IMNV‐infected cells was obtained on 10 day post‐infection (d p.i.), whereas the higher CT value of 35.21 was obtained in IMNV‐infected cells on 2 d p.i. There is no significant difference between CT values of IMNV production in vitro using C6/36 cell line and in vivo using shrimp. The IMNV propagated in C6/36 cells is capable of infecting shrimp and caused 100% mortality in shrimp. Clinical signs observed in shrimp injected with IMNV propagated in C6/36 cell line were found to be similar to naturally infected shrimp.